2020
DOI: 10.1002/jor.24701
|View full text |Cite
|
Sign up to set email alerts
|

Can measurements from an anteroposterior radiograph predict pelvic sagittal inclination?

Abstract: Pelvic sagittal inclination (PSI) is often evaluated in patients with hip pathology using lateral radiographs. However, it would be useful if PSI could be predicted from an anteroposterior radiograph since this film is ubiquitous in the evaluation of hip pathology. Herein, computer‐modeling was applied to predict PSI from radiographic measurements assessed in the anteroposterior plane. Three‐dimensional surface models of the pelvis, femur, and sacrum were reconstructed from computed tomography images of 50 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
0
17
2
Order By: Relevance
“…Tamura et al 32 also reported differences in orientation of the pelvis between supine and standing differences. Further, PT is known to change between standing and supine positions, although the difference is highly correlated ( r = .82) 33 . It is possible these observations may explain some of the differences we found in our results when compared to prior reports.…”
Section: Discussioncontrasting
confidence: 46%
“…Tamura et al 32 also reported differences in orientation of the pelvis between supine and standing differences. Further, PT is known to change between standing and supine positions, although the difference is highly correlated ( r = .82) 33 . It is possible these observations may explain some of the differences we found in our results when compared to prior reports.…”
Section: Discussioncontrasting
confidence: 46%
“…Tannast et al 26 . and Uemura et al 35 . showed that only the SSc distance had a moderately strong positive correlation with PST, which could be found for all patients based on a large group.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, AP pelvic radiographs remain the standard of care imaging modality for pre and postoperative assessment during THA owing to easy accessibility, cost effectiveness, low radiation exposure, and widespread availability, 18,26,33,36 and the use of AP radiographs to assess changes in pelvis has been validated, 34,37 which proved that the position and radiographic methods we used in this study was appropriate. And radiographic overlap could occur in a lateral position between right and left hips, making the diagnostic evaluation complicated and less efficient 18,35,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study had some limitations. Because it is generally believed that it is difficult to measure sagittal or axial pelvic tilt from the anteroposterior view of the pelvis 19 , concerns remain about the measurement error on TPP images. In fact, it is almost impossible to accurately measure axial pelvic tilt from the anteroposterior view of the pelvis.…”
Section: Discussionmentioning
confidence: 99%